Prevalence and factors related to orthostatic syndromes in recently diagnosed, drug-naïve patients with Parkinson disease - Capani, Francisco (2020)
Fil: Capani, Francisco. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.